Plan de negocios de Hostería Llano de los Vientos en la ciudad de Baños de Agua Santa, provincia del Tungurahua - Vieira Herrera, Gandhi Rafael (2014)
The steady growth of tourism in the city of Baños de Agua Santa generates high tourist lodgings and accommodation. This fact justifies the creation of a new Hosteria that gives the community a new hotel infrastructure with efficient service, in a quiet, environmentally friendly and comfortable environment so the business plan of the Llano Hosteria Vientos proposed in this document. The physical and organizational development of this new Hosteria would undoubtedly improve the tourism image of the region, contributing in various ways to the economic growth of their inhabitants; to provide work places, thus encompassing the social, labor and tourism aspects. In this work a model business plan to continue to implement a hostel in Baños de Agua Santa exposing all components that are necessary for their efficient operation in both the legal, administrative and operational aspects is provided. It concludes by making a financial feasibility analysis of the project